To solve the quadratic equation \((x + 27)^2 - 6 = -3\), we can first simplify the equation.
-
Add 6 to both sides: \[ (x + 27)^2 - 6 + 6 = -3 + 6 \] \[ (x + 27)^2 = 3 \]
-
Take the square root of both sides: \[ x + 27 = \pm \sqrt{3} \]
-
Isolate \(x\): \[ x = -27 \pm \sqrt{3} \]
Now we have two possible solutions:
-
\(x = -27 + \sqrt{3}\)
-
\(x = -27 - \sqrt{3}\)
-
Calculating the values:
-
For \(x = -27 + \sqrt{3}\): \[ x \approx -27 + 1.732 \approx -25.268 \]
-
For \(x = -27 - \sqrt{3}\): \[ x \approx -27 - 1.732 \approx -28.732 \]
-
-
Rounding to the nearest hundredth:
- \(x \approx -25.27\)
- \(x \approx -28.73\)
Thus, the solutions to the equation are: \[ x \approx -25.27 \quad \text{and} \quad x \approx -28.73 \]